Person Pronoun Deixis in Indonesian Cellular Operators Advertisements: Represent the Participants? - Ningrum Novitasari; Yulia Mutmainnah; Yunita Nugraheni (Universitas Muhammadiyah Semarang, 2017)
This qualitative descriptive research uses non participatory observation method with Telkomsel and Indosat cellular operator advertisements as the objects. There are three types of person pronoun deixis: first, second and third person pronoun deixis which are consist of 14 deixis, namely: ku, aku, aku, gue, kita, kami, mu, kamu, kamu, loe, kamu, bang, dia, dan mereka. The most commonly person pronoun deixis used in Telkomsel and Indosat advertisements is